Sugary beverages intake and risk of chronic kidney disease: the mediating role of metabolic syndrome - Dai, Xiao-Yu; Chen, Xiang-Yu; Jia, Li-Na; Jing, Xiao-Tong; Pan, Xiao-Yan; Zhang, Xing-Yu; Jing, Zhong; Yuan, Jin-Qiu; He, Qiang-Sheng; Yang, Li-Ling (Frontiers in Nutrition, 2024)
Background: Although several studies linked the sugary beverages to chronic kidney disease (CKD), the role of different types of sugary beverages in the development of CKD remained inconsistent. This study aimed to examine the associations of sugar-sweetened beverages (SSBs), artificially-sweetened beverages (ASBs), and natural juices (NJs) with CKD risk, and assess the extent to which the associations were mediated through metabolic syndrome (MetS).Methods: This is a prospective analysis of 191,956 participants from the UK Biobank. Participants with information on beverage consumption and no history of CKD at recruitment were included. Daily consumptions of SSBs, ASBs and NJs were measured via 24-h dietary recall. Cox models were fitted to calculate the hazard ratios (HRs) and confidence intervals (CIs) of sugary beverages intakes on CKD risk. The causal mediation analyses were conducted to investigate whether MetS explained the observed associations.We documented 4983 CKD cases over a median of 10.63 years follow-up. Higher consumption of SSBs and ASBs (>1 units/d compared with none) was associated with an elevated risk of CKD (HR: 1.45; 95% CI: 1.30 -1.61, P-trend<0.001 for SSBs and 1.52, 95% CI: 1.36-1.70 for ASBs). In contrast, we observed a J-shaped association between NJs and CKD with the with lowest risk at 0-1 unit/day (0-1 unit/d vs 0, HR 0.86; 95% CI 0.81-0.91). The proportions of the observed association of higher intakes of SSBs and ASB with CKD mediated by MetS were 12.5% and 18.0%, respectively.Conclusions: Higher intakes of ASBs and SSBs were positively associated with the development of CKD, while moderate consumption of NJs was inversely associated with CKD risk. More intensified policy efforts are warranted to reduce intake of SSBs and ASBs for CKD prevention.